(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The publication highlights issues regarding the current state of regulatory and organizational support for planning and control processes in the Ministry of Internal Affairs of Ukraine, as well as in central executive bodies whose activities are directed through the Minister of Internal Affairs of Ukraine. An analysis of domestic and foreign scientific literature on the issue of planning and control in the public management system has been conducted. It has been proven that regulatory and legal regulations and provisions relating to the legal status of units responsible for the specified processes require appropriate optimization and improvement. In particular, internal discrepancies in the content of orders of the Ministry of Internal Affairs, National Police, State Emergency Service, National Guard of Ukraine on planning and control issues have been identified. The absence of institutional orders on the construction of an internal control system in the structure of the Ministry of Internal Affairs and National Police has been emphasized. The directions for improving the regulatory and organizational support of the planning and control processes in the public management system of the bodies and divisions of the Ministry of Internal Affairs are proposed, in particular, in terms of adopting institutional regulatory and legal acts on the planning and internal control system, in particular departmental orders on the introduction of unified approaches, standards, procedures for planning and internal control, bringing the norms of existing departmental documents in accordance with the rules of legislative technique. A list of principles on the basis of which planning and control activities in the Ministry of Internal Affairs system should be carried out is given. The need to develop and adopt documents related to the strategic development of the Ministry of Internal Affairs system taking into account the requirements of the legal regime of martial law is emphasized: strategies for the development of the Ministry of Internal Affairs system taking into account the requirements of martial law, strategies for the development of other central executive bodies of the Ministry of Internal Affairs.